PENGARUH METODE MENGAJAR DENGAN MENGONTROL MOTIVASI TERHADAP PRESTASI BELAJAR - Muhammad Ali Gunawan (LPPM Universitas Pekalongan, 2011)
The aim of this research is to find out: The difference of learning achievement between students who is taught using inquiry method and others who use task-based method and direct method using media in the Mathematic Statistic I subject in Mathematics Education Program Pekalongan University after controlling using motivation variable. The research is done towards all fifth semester students which are 114 people (30 people IV A class, 36 people IV B class and 48 people). Data analysis used is covariant analysis (ancova 1 line). The result of this research showed that: 1) after controlling by motivation variable, there is the difference of learning outcome between students who is taught using inquiry method and others who use task-based method and direct method using media. Where the result from covariant analysis showed the significance 0,000 less than α = 0,05 which is determined; 2) after controlling by motivation variable , students who is taught inquiry method is 77.69 better than students who is taught direct method using media with the score of learning outcome in 67,95 better than the students who is taught by using task- based method with the score in 62,29.